Candida albicans Impacts Staphylococcus aureus Alpha-Toxin Production via Extracellular Alkalinization - Olivia A. Todd (American Society for Microbiology, 2019)
ABSTRACT Candida albicans and Staphylococcus aureus are common causes of nosocomial infections with severe morbidity and mortality. Murine polymicrobial intra-abdominal infection (IAI) with C. albicans and S. aureus results in acute mortality dependent on the secreted cytolytic effector alpha-toxin. Here, we confirmed that alpha-toxin is elevated during polymicrobial growth compared to monomicrobial growth in vitro. Therefore, this study sought to unravel the mechanism by which C. albicans drives enhanced staphylococcal alpha-toxin production. Using a combination of functional and genetic approaches, we determined that an intact agr quorum sensing regulon is necessary for enhanced alpha-toxin production during coculture and that a secreted candidal factor likely is not implicated in elevating agr activation. As the agr system is pH sensitive, we observed that C. albicans raises the pH during polymicrobial growth and that this correlates with increased agr activity and alpha-toxin production. Modulation of the pH could predictably attenuate or activate agr activity during coculture. By using a C. albicans mutant deficient in alkalinization (stp2Δ/Δ), we confirmed that modulation of the extracellular pH by C. albicans can drive agr expression and toxin production. Additionally, the use of various Candida species (C. glabrata, C. dubliniensis, C. tropicalis, C. parapsilosis, and C. krusei) demonstrated that those capable of raising the extracellular pH correlated with elevated agr activity and alpha-toxin production during coculture. Overall, we demonstrate that alkalinization of the extracellular pH by the Candida species leads to sustained activation of the staphylococcal agr system. IMPORTANCE Candida albicans and Staphylococcus aureus are commonly coisolated from central venous catheters and deep-seated infections, including intra-abdominal sepsis. Thus, they represent a significant cause of nosocomial morbidity and mortality. Yet how these organisms behave in the context of polymicrobial growth remains poorly understood. In this work, we set out to determine the mechanism by which activation of the staphylococcal agr quorum sensing system and production of its major virulence effector alpha-toxin is enhanced during coculture with C. albicans. Surprisingly, we likely ruled out that a secreted candidal factor drives this process. Instead, we demonstrated that alkalinization of the extracellular milieu by C. albicans and other Candida species correlated with elevated agr activity. Thus, we propose a mechanism where modulation of the extracellular pH by fungal opportunists can indirectly alter virulence of a bacterial pathogen. Uncovering molecular events that drive interkingdom pathogenicity mechanisms may enhance surveillance and treatment for devastating polymicrobial infections.